Understanding Open Access When, Why & How to Make Your Work Openly Accessible - Rubow, Lexi (Authors Alliance, 2016)
Understanding Open Access: When, Why & How to Make Your Work Openly Accessible provides a scholarly author-oriented look at the ins and outs of open access publishing. The guide addresses common concerns about what "open access" means, how institutional and funder open access policies work, and why authors might consider making their works openly accessible online. It also provides information on how to openly license works, how to tailor licensing permissions, and where authors can consider making their open access works available. The guide includes real-life strategies that authors can use to work with publishers, institutions, and funders to make their works available on the terms most consistent with their dissemination goals.